2018
DOI: 10.1051/matecconf/201823202001
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Image Segmentation Methods for Lung Nodule Detection Based on Computed Tomography Images

Abstract: The detection and segmentation of lung nodules based on computer tomography images (CT) is a basic and significant step to achieve the robotic needle biopsy. In this paper, we reviewed some typical segmentation algorithms, including thresholding, active contour, differential operator, region growing and watershed. To analyse their performance on lung nodule detection, we applied them to four CT images of different kinds of lung nodules. The results show that thresholding, active contour and differential operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Segmentation of these lesions was found to be less complicated compared to that of mediastinal masses, because it is only attached to a smooth surface like the chest wall, in comparison to complicated structures such as the esophagus, trachea, thymus, or aorta for a mediastinal lesion. Conventional boundary‐ and energy‐based delineation such as Canny edge detector and active contour, have failed to accurately segment pleural wall masses with very high false positive rates . This study has reported that the chest wall was also falsely segmented along with the nodule using these models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Segmentation of these lesions was found to be less complicated compared to that of mediastinal masses, because it is only attached to a smooth surface like the chest wall, in comparison to complicated structures such as the esophagus, trachea, thymus, or aorta for a mediastinal lesion. Conventional boundary‐ and energy‐based delineation such as Canny edge detector and active contour, have failed to accurately segment pleural wall masses with very high false positive rates . This study has reported that the chest wall was also falsely segmented along with the nodule using these models.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al demonstrated that energy‐based models (level set, graph‐cut) and machine learning‐based models (U‐Net, CF‐CNN) have efficiently segmented solitary masses, with sensitivity ranging from 64%‐92% . Zheng et al investigated four classes of segmentation algorithms, namely, intensity‐based (Otsu), region‐based (region growing, watershed transform), edge‐based (Canny detector) and energy‐based (active contour); and have qualitatively shown that all methods yield between good to excellent results; except for the watershed transform, which had the highest false negative rate. We present two examples from our datasets, as depicted in Figures and , for the solitary mass segmentation from subjects 024 and 051.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphological methods including thresholding method [4,5], region growing [6,7], active contours [8,9], and graph-cut methods [10,11], are often based on pixel density; whereas deep learning-based methods [12,13] use neural networks to extract semantic information [14]. Although morphological techniques do not necessitate as much processing as DNN, their absence of deep semantic traits and 3D information might result in incorrect segmentation, particularly for juxtapleural [9], ground-glass, and small-sized nodules [15]. To put it another way, their effects are size [5] or type dependent.…”
Section: Introductionmentioning
confidence: 99%